Implementation of Water Filtration Method with Solar Power Plant for Residents of Gomang Hamlet Lajolor Village - RM. Armaya Mangkunegara; Sulistyani Eka Lestari; Maja Pranata Marbun; Dhina Mustikaningrum (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
This service program aims to optimize natural resources through water filtration installations by converting solar power into electrical energy to meet the clean water needs of Gomang hamlet - Lajolor Village residents. The method used to carry out community service is service and mentoring. Technical implementation is divided into three stages: preparation, implementation, monitoring, and evaluation. At each stage of implementation, instruments that refer to the objectives of the service based on the results of observations in the field are used. The results of this service program are in the form of using PLTS to replace electricity needs to drive pumps and filtration equipment to provide safe, healthy, and clean water for residents of Gomang Hamlet. In the long term, it can also be improved in the form of mineral water packaging to enhance the economy of residents. This program also produces outputs in the form of maintaining a sustainable ecology, especially in supporting the sustainability of spring water sources. The Water Filtration Program with PLTS can optimize the water supply produced from the abundant springs in Gomang Hamlet - Lajolor Village and increase residents' income by cultivating healthy living. The implementation of this program requires assistance and sufficient time. Optimization of limited time has not been able to provide maximum results. Therefore, this program needs to be implemented continuously. Local community groups and related parties enthusiastically followed the community service activities in Gomang hamlet. Nevertheless, the participation of various parties in supporting the program's implementation is needed in the future.